Organic TFTs Using Iodine Treated Pentacene Film with High-k Dielectric Nd2O3. (4th September 2015) - Saikia, Dipok; Saikia, P. K.
Abstract : Organic Thin Film Transistors (OTFT) have been studied with iodine treated pentacene semiconductor. Rare earth oxide Nd2 O3 is used as gate insulator. The treatment of iodine improves the mobility of the OTFTs while use of high dielectric constant oxide as gate insulator reduces the threshold voltage. The fabricated OTFTs show good I-V characteristics, low threshold voltage and high field effect mobility. The mobility of the pentacene OTFTs is highly improved due to the iodine treatment. Long time iodine treatment have negative effect on current ON-OFF ratio.